Tying Odysseus to the Mast: Evidence from a Commitment Savings Product in the Philippines - Nava Ashraf; Dean S. Karlan; Wesley Yin (Yale University, Economic Growth Center, 2005)
We designed a commitment savings product for a Philippine bank and implemented it using a randomized control methodology. The savings product was intended for individuals who want to commit now to restrict access to their savings, and who were sophisticated enough to engage in such a mechanism. We conducted a baseline survey on 1777 existing or former clients of a bank. One month later, we offered the commitment product to a randomly chosen subset of 710 clients; 202 (28.4 percent) accepted the offer and opened the account. In the baseline survey, we asked hypothetical time discounting questions. Women who exhibited a lower discount rate for future relative to current tradeoffs, and hence potentially have a preference for commitment, were indeed significantly more likely to open the commitment savings account. After twelve months, average savings balances increased by 81 percentage points for those clients assigned to the treatment group relative to those assigned to the control group. We conclude that the savings response represents a lasting change in savings, and not merely a short-term response to a new product.
Keywords: C93; D01; D11; D12; D14; D81; D91; G11; O12; 330; Savings; commitment; hyperbolic preferences; microfinance; development economics; program evaluation; field experiment; self-control; Sparen; Zeitpräferenz; Philippinen; Mikrofinanzierung; Feldforschung